How Do Economic Conditions Influence Support for Democracy? - Amri, Puspa D. (Universitas Islam Internasional Indonesia (UIII), 2023)
Abundant political economy work has found that societies tend to be less supportive of the political system that governs their country when the economy deteriorates. This paper seeks to enrich the existing literature on economic and democratic assessments by including the relatively under-explored group of developing countries in the Middle East and North Africa (MENA) region, many of which are Muslim countries. Using public opinion data from the World Values Survey of 78 countries from 2005 to 2020, the author applies multi-level regressions to test whether the relationship between democratic support and economic growth varies along three dimensions: country affluence, MENA versus non-MENA regions, and type of political regime. Consistent with past studies, the findings in this paper confirm that higher real gross domestic product (GDP) per capita growth significantly enhances public support for democracy. However, it also identifies that the more robustly significant predictors of public support for democracy are political variables, particularly evaluation of government performance. The interaction variables analysis reveals that the effects of economic growth on public support for democracy is weaker in the presence of higher country affluence as well as in more liberal democracies, while being located in the MENA region strengthens the relationship between economic growth and public support for democracy. In addition, respondents who consider free and fair elections as well as protection of civil liberties to be essential features of democracy tend to be more supportive of democracy itself. Meanwhile, those who associate democracy with redistributive policies tend to have a more negative assessment of democracy.